Diversificação econômica : análise da estrutura setorial das microrregiões do sul do Brasil, 2002/2010 - Moreira, élisson Telles (2014)
The aim of this work is to examine in exploratory way the economic diversity of the microregions of southern Brazil in two periods: 2002 and 2010. The study uses information from formal employment, obtained in the Annual Report of Social Information (RAIS), for a set of 25 sub-sectors of the Brazilian Institute of Geography and Statistics (IBGE), distributed in 94 South Brazilian microregions. The research uses both the entropy and Herfindahl indexes to calculate diversity for each of the South Brazilian microregions. It evaluates together employment levels with shift-share technique the relevance of national, sectoral and competitive effects on regional economic growth, and utilizes Pavitt taxonomy for evaluates the most technological localities. The results indicate that the most diversified regions are those with large populations. Overall, the micro-regions analyzed showed positive results in Industry Mix, highlighting the microregions of Santa Catarina and Parana.